2013
DOI: 10.1039/c2cc37227d
|View full text |Cite
|
Sign up to set email alerts
|

A clocked finite state machine built from DNA

Abstract: We implement a finite state machine by representing state, transition rules and input symbols with DNA components. Transitions between states are triggered by a clock signal which allows synchronized, parallel operation of two (or more) state machines. The state machine can be re-programmed by changing the input symbols.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 24 publications
0
16
0
Order By: Relevance
“…5a. The design is based on that of Costa Santini et al 10 , but here the finite state machine is immobilized on the surface and there is no molecular clock. In our system activated dumb-bell hairpins can bind to the immobilized state machines, and the transition rule then binds to the domain formed by the conjunction of the initial state domain of the state machine and the identity domain of the hairpin gate.…”
Section: Operating a Finite State Machine Using The Dumb-bell Logic Gmentioning
confidence: 99%
See 1 more Smart Citation
“…5a. The design is based on that of Costa Santini et al 10 , but here the finite state machine is immobilized on the surface and there is no molecular clock. In our system activated dumb-bell hairpins can bind to the immobilized state machines, and the transition rule then binds to the domain formed by the conjunction of the initial state domain of the state machine and the identity domain of the hairpin gate.…”
Section: Operating a Finite State Machine Using The Dumb-bell Logic Gmentioning
confidence: 99%
“…It has been shown that 'see-saw' gates 5 can be used for thresholding and the construction of complex DNA computing systems that are capable of performing arithmetic functions 6 or demonstrating memory and inference 7 . Other DNA computing paradigms include chemical reaction networks 8 , finite state machines 9,10 or algorithmic self-assembly of tiles 11 , and it was recently demonstrated that DNA could be used to implement a non-deterministic universal Turing machine 12 . The capabilities of DNA computing machines could be broadened further via their integration with electronic systems, which could underpin new approaches for input, processing and readout 13 .…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that ‘see-saw’ gates [ 18 ] can be used for thresholding and the construction of complex DNA computing systems that are capable of performing arithmetic functions [ 19 ] or demonstrating memory and inference [ 20 ]. Other DNA computing paradigms include chemical reaction networks [ 21 ], finite state machines [ 22 , 23 ] or algorithmic self-assembly of tiles [ 24 ], and it was recently demonstrated that DNA could be used to implement a non-deterministic universal Turing machine [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Besides, only a few of transition metal complexes containing bis(5-methyl-1H-pyrazole-3-carboxylic acid)alkane ligands have been reported. [21][22][23] (3, 2D) and [Pb(L 2 )(2,2'-bpy)] 2n ·9nH 2 O (4, 1D) were isolated therefrom. In this paper, the synthesis, crystal structures and luminescent properties of the compounds 1-5 were described.…”
Section: Introductionmentioning
confidence: 99%